2013
DOI: 10.1111/jdv.12306
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy and cost‐effectiveness of dermoscopy in primary care: a cluster randomized clinical trial

Abstract: The probability of a correct diagnosis was 1.25 times higher using a dermoscope than without a dermoscope. Although this difference is marginally not statistically significant, dermoscopy in general practice appears to be cost effective. We therefore think that GPs should be trained to use a dermoscope, although they should realize that even with the use of a dermoscope not all lesions will be diagnosed correctly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(77 citation statements)
references
References 20 publications
1
75
0
1
Order By: Relevance
“…The survey was addressed to dermatologists, as they are the main users of dermoscopy across all European countries. While the extension of dermoscopy training to general practitioners or specialized nurses is considered by some countries, this practice is still nascent in most parts of the European continent and could be considered for future research.…”
Section: Discussionmentioning
confidence: 99%
“…The survey was addressed to dermatologists, as they are the main users of dermoscopy across all European countries. While the extension of dermoscopy training to general practitioners or specialized nurses is considered by some countries, this practice is still nascent in most parts of the European continent and could be considered for future research.…”
Section: Discussionmentioning
confidence: 99%
“…In practice, we believe the level of required diagnostic accuracy for the application should be higher than that of a regular GP, [16][17][18] and as close as possible to that of a dermatologist. Two recent studies compared the sensitivity of dermatologists and a machine learning algorithm to detect skin cancer, against histopathology.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is little evidence to confirm the optimal training modality and duration. Educational interventions in previous randomized controlled trials have ranged from a single hour to 10 h plus further textbook reading or e‐learning . However, there is no randomized controlled trial evidence comparing the effects of shorter and longer training periods.…”
Section: Discussionmentioning
confidence: 99%
“…Educational interventions in previous randomized controlled trials have ranged from a single hour 21 to 10 h plus further textbook reading or e-learning. 39 However, there is no randomized controlled trial evidence comparing the effects of shorter and longer training periods. Previous studies have found that perceived training requirements are amongst the most commonly cited barriers to implementation of dermoscopy.…”
Section: Comparisons With Existing Literaturementioning
confidence: 99%